CME Update: Management of Post-Traumatic Stress Disorder (PTSD) in Rural Family Practice - Cook, Jolene (UBC Journal of Family Practice Research and Scholarship, 2015)
Background: Post-traumatic stress disorder (PTSD) can present in family practice in a variety of situations. For example, physical and sexual abuse in residential schools has left many first nations people with what some call chronic PTSD. Other patients with PTSD have been victims of natural disaster or simply were involved in motor vehicle accidents. Too often these patients do not receive proper treatment early on and develop addictions to benzodiazapines or other substances of abuse. Being able to recognize and manage this disorder in family practice is valuable to help earlier recovery and prevent poor long-term outcomes. However, getting timely access to a psychiatrist or cognitive behavior therapy can be difficult, particularly in a rural family practice setting.Objective: How can we as family physicians manage PTSD in rural or remote communities?Methods: Pubmed search under MESH heading "PTSD" with limits of randomized control trial, metanalysis, clinical guidelines, adults and published in last five years. Results were then cross-searched with "rural" both with limits set on and off. A Cochrane database search was done using "PTSD/post-traumatic stress disorder" as well.Results: pending.Conclusions: pending.